Appreciation of The Qur'an for Knowledge Able People (Study of Verses on science in the Qur'an) - Basri Mahmud; Hamzah Hamzah (JIA (Jurnal Ilmu Agama), 2023)
This study aims to reveal the meaning of knowledge, the source of knowledge, and the process of obtaining it as well as God's appreciation for those who have knowledge based on the interpretation of the verses of the Qur'an. There are two types of data used, namely primary data in the form of qurani data, while secondary data in the form of supporting data related to this study. Data processing consists of data organization, verification, transformation, merging and sorting information mainly based on chronology and then analyzing the use through qualitative methods so that a more precise and systematic is born. The results of this study show that the word science with its various derivatives is repeated in the Qur'an 854 times. Science is one of the qualities of Allah, therefore this trait is called al-Alim (All-Knowing). He is the source of knowledge and all the knowledge that man gains from him is knowledge gained through various efforts or the so-called kasbi science or knowledge gained without effort called ladunni science. Then God rewarded those who were knowledgeable by appointing him as caliph on this earth, forbidding him to follow something without knowledge and bestowing it upon him a high degree.